Electrocardiographic Features of Left Ventricular Diastolic Dysfunction and Heart Failure With Preserved Ejection Fraction: A Systematic Review - Van Ommen, Anne-Mar; Kessler, Elise Laura; Valstar, Gideon; Onland-Moret, N. Charlotte; Cramer, Maarten Jan; Rutten, Frans; Coronel, Ruben; Den Ruijter, Hester (Frontiers in Cardiovascular Medicine, 2021)
Background Electrocardiographic (ECG) features are well known for heart failure with reduced ejection fraction (HFrEF), but not for left ventricular diastolic dysfunction (LVDD) and heart failure with preserved ejection fraction (HFpEF). As ECG features could help to identify high-risk individuals in primary care, we systematically reviewed the literature for ECG features diagnosing women and men suspected of LVDD and HFpEF. Methods and results Of the 6,371 records identified, only 9 studies reported diagnostic measures, of which 8 studied LVDD. For LVDD, most promising features were T end-P/(PQ*age), which is the electrocardiographic equivalent of passive-to-active filling (AUC: 0.91-0.96), and repolarization times (QTc interval ≥350ms, AUC: 0.85). For HFpEF, the Cornell product ≥1800 mm*ms showed poor sensitivity of 40% (AUC: 0.62). No studies presented results stratified by sex. Conclusion ECG features are not widely evaluated in diagnostic studies for LVDD and HFpEF. Only for LVDD, two ECG features related to the diastolic interval, and repolarization measures showed diagnostic potential. To improve diagnosis and care for women and men suspected of heart failure, reporting of sex-specific data on ECG features is encouraged.